Method for extracting carbide in wear-resistant steel

By using electrolytes configured with tartaric acid, potassium chloride and deionized water in wear-resistant steel for electrolytic extraction, combined with the isolation technology of nylon filter membrane, the problem of impurity pollution during carbide extraction in wear-resistant steel is solved, and the problem of impurity pollution in the carbide extraction process is achieved. Carbide extraction with high purity.

CN119394754AActive Publication Date: 2025-02-07KUNMING UNIV OF SCI & TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411517921.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-07
Estimated Expiration
2044-10-29

AI Technical Summary

Technical Problem

The prior art is difficult to effectively extract carbides from wear-resistant steels, and impurities are easily mixed in during electrolytic extraction, affecting the purity of carbides.

Method used

The electrolyte is configured with tartaric acid, potassium chloride and deionized water, and electrolytic extraction is performed through an H-type exchangeable membrane electrolytic cell. A nylon filter membrane is used to isolate the iron ions on the cathode to avoid impurity contamination.

Benefits of technology

High purity extraction of carbides is achieved, the amount of reagent added is reduced, the operation steps are simplified, and the carbide loss is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119394754A_ABST
    Figure CN119394754A_ABST
Patent Text Reader

Abstract

The invention discloses a method for extracting carbides in wear-resistant steel, and belongs to the technical field of metal electrochemistry. According to the method, the purpose of extracting pure and complete carbides in steel is achieved by improving the electrolyte and the method, the electrolyte containing tartaric acid is selected and reacts with metal ions in the solution to inhibit generation of ferric hydroxide, sulfide inclusions can be effectively dissolved in the acid environment, and the influence of the impurities on the purity of the carbides is reduced; an H-type electrolytic tank is adopted, a filter membrane is used for separating a cathode from an anode through a physical means, and iron separated out of the cathode is effectively prevented from being mixed into carbide to affect analysis of the carbide; according to the method, the carbide in the wear-resistant steel matrix can be successfully obtained by selecting the proper electrolyte and the electrolytic extraction device, the extraction device is simple, the obtained carbide is purer and more complete, and analysis on phase, morphology and particle size distribution of the carbide can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal electrochemistry, and in particular relates to a method for extracting carbides from wear-resistant steel. Background Art

[0002] Wear-resistant steel forms carbides in the matrix by adding strong carbide elements, and its comprehensive mechanical properties are improved by the precipitation strengthening mechanism; however, factors such as the number, morphology and size of carbides will affect the mechanical properties of steel, so it is necessary to study the carbides in steel; the three-dimensional carbide morphology cannot be observed only through metallographic microscopes and scanning electron microscopes, and the carbides are not evenly distributed in the matrix. The number and size of carbides obtained by image statistics are very random, and it takes a lot of work to reduce this randomness. Therefore, it is of great significance to use electrolytic extraction to extract the carbides in the matrix for research.

[0003] Utilizing the electrolytic potential difference between the steel matrix and the carbide, with the steel sample as the anode and the platinum electrode as the cathode, after applying a constant voltage, the steel matrix begins to dissolve in an ionic state, while the carbide in the matrix is ​​retained due to the relatively high electrolytic potential, attached to the surface of the matrix or dispersed in the solution; however, during the electrolysis process, the iron ion content increases, and iron hydroxide is easily formed, and a reduction reaction is easily generated on the cathode surface to produce iron. At the same time, some inclusions are difficult to dissolve during the electrolysis process, and are easily mixed into the carbide during the collection process and collected together, which affects the purity of the carbide. Summary of the invention

[0004] The object of the present invention is to provide a method for extracting carbides from wear-resistant steel, which specifically comprises the following process steps:

[0005] (1) Prepare the electrolyte using tartaric acid, potassium chloride and deionized water.

[0006] (2) The wear-resistant steel sample was prepared as the electrolytic sample required for electrolytic extraction. The oxide on the surface of the wear-resistant steel sample was removed using 240-2000 mesh sandpaper. The sample was ultrasonically cleaned in a beaker containing anhydrous ethanol for 5-10 minutes and then dried and weighed.

[0007] (3) An H-type replaceable membrane electrolytic cell was used and three electrodes were installed. Two nylon filter membranes were fixed at the flange ports. The flange ports at both ends were fixed with flange clamps. The working electrode was connected to the positive pole of the power supply as the anode, and the platinum electrode was used as the cathode. The electrolytic extraction was performed using a constant voltage polarization mode.

[0008] (4) After the electrolysis is completed, the sample is placed in a container filled with anhydrous ethanol, and then placed in an ultrasonic dispersion, and the process is repeated 2 to 3 times; the anhydrous ethanol containing carbides is transferred to a suction filtration device; the electrolyte containing carbides at the working electrode end is also transferred to the suction filtration device; and the residual carbides on the nylon filter membrane of the container, electrolytic cell and working electrode end are washed into the suction filtration device using anhydrous ethanol.

[0009] (4) The remaining sample surface is cleaned and dried, and the weight of the sample after electrolytic extraction is obtained by weighing; the anode mud produced during the electrolysis process is filtered out, and it is rinsed with anhydrous ethanol for 4 to 5 times during the filtration process to obtain pure carbide on the nylon filter membrane, and the nylon filter membrane containing the carbide is placed in a drying oven for drying, and the obtained carbide is collected and weighed.

[0010] Preferably, in step (1) of the present invention, every 500 mL of electrolyte is prepared according to the ratio of 25-30 g of tartaric acid, 15-20 g of potassium chloride, and the balance is deionized water.

[0011] Preferably, the temperature of the electrolytic cell in step (3) of the present invention is maintained at room temperature, the voltage of the constant voltage polarization mode is set to 3.4 to 3.8 V, and the electrolysis time is set to 6 to 12 h.

[0012] Preferably, the nylon filter membrane used in step (3) and step (5) of the present invention has a pore size of Φ0.05 μm.

[0013] Preferably, the electrolyte used in the present invention needs to be prepared and used immediately, and the purity of tartaric acid and potassium chloride is analytical grade.

[0014] Preferably, the steel sample used in step (2) is a thin block steel sample with a size of 10 mm×15 mm×2 mm, and the steel sample is fixed with a platinum sheet electrode clamp for use as a working electrode.

[0015] Preferably, each H-type electrolytic cell in step (3) has a capacity of 100 mL and an inner diameter of the flange opening of 15 mm.

[0016] Preferably, the H-type electrolytic cell in step (3) isolates the working electrode from the platinum electrode, and the iron generated by reduction on the platinum electrode is separated by a nylon filter membrane, which effectively prevents the carbide from being contaminated by iron. The installation process of using this device is simple and quick.

[0017] Preferably, the flange in step (3) uses two overlapping nylon filter membranes to facilitate the collection of carbides released onto the filter membranes.

[0018] Preferably, the vacuum pump used for filtration in step (4) has a suction flow rate of 15 L / min.

[0019] Preferably, in step (4), the drying temperature of the drying oven is 80° C. and the drying time is 15 min.

[0020] Preferably, when collecting carbides in step (4), carbides of each part are collected on a filter membrane to obtain all carbides of the electrolyzed part of the sample, which can be used for analyzing the content of carbides.

[0021] Beneficial effects of the present invention:

[0022] The electrolyte of the present invention has simple ingredients, is economical and environmentally friendly, can not only destroy the passivation film on the surface of the steel sample and reduce current attenuation, but also react with iron ions to avoid the formation of precipitates during the electrolysis process to affect the purity of the collected carbides, and ionizes hydrogen ions to make the electrolyte acidic. A small amount of manganese sulfide inclusions in the steel will decompose in this acidic environment and react with tartaric acid to avoid being collected as carbides.

[0023] In summary, the present invention reduces the addition of reagents and obtains pure carbide by optimizing the electrolyte composition; the present invention also simplifies the operation steps and reduces the carbide loss during the transfer process by optimizing the extraction device. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Schematic diagram of the electrolytic extraction device used in the present invention.

[0025] Figure 2 Schematic diagram of the suction filtration device used in the present invention.

[0026] Figure 3 This is an electron microscope image of the carbide in Example 1.

[0027] Figure 4 This is the XRD pattern of the carbide in Example 1.

[0028] Figure 5 This is the particle size distribution diagram of the carbide in Example 1.

[0029] Figure 6 This is an electron microscope image of the carbide in Example 2.

[0030] Figure 7 This is the XRD diagram of the carbide in Example 2.

[0031] Figure 8 This is the particle size distribution diagram of the carbide in Example 2.

[0032] Fig. 9 This is an electron microscope image of the carbide in Example 3.

[0033] Fig.10 This is the XRD diagram of the carbide in Example 3.

[0034] Fig.11 This is the particle size distribution diagram of the carbide in Example 3.

[0035] Fig.12 This is the XRD pattern of the carbide in Comparative Example 1.

[0036] Fig.13 This is the XRD diagram of the carbide in Comparative Example 2. DETAILED DESCRIPTION

[0037] The present invention is further described in detail below in conjunction with the accompanying drawings and specific implementation methods, but the protection scope of the present invention is not limited to the described contents.

[0038] Example 1

[0039] This embodiment uses austenitic wear-resistant steel as the working electrode of electrolytic extraction, which specifically includes the following steps:

[0040] (1) Preparation of electrolyte: The electrolyte is prepared according to the ratio of 30 g tartaric acid, 20 g potassium chloride, and 500 mL deionized water.

[0041] (2) Use 240-2000 mesh sandpaper to remove oxides from the surface of the wear-resistant steel sample, place it in a beaker filled with anhydrous ethanol and ultrasonically clean it for 10 minutes, dry the sample and weigh and record the sample weight. Prepare eight samples with a total mass of 16.7274 g.

[0042] (3) Install a working electrode and a reference electrode at one end of a 100 mL H-type replaceable membrane electrolytic cell, install a platinum electrode at the other end, fix two nylon filter membranes at the flange, and use flange clamps to fix the flanges at both ends; after the installation is completed, pour the electrolyte prepared in step (1) into the cell to immerse the three electrodes and the flange connection; connect the working electrode to the positive pole of the power supply as the anode, and the platinum electrode as the cathode, and keep the temperature of the electrolyte at room temperature; use a constant voltage polarization mode for electrolytic extraction, set the voltage to 3.8 V, the electrolysis time to 8 h, and start electrolysis.

[0043] (4) After all samples are electrolyzed, the samples are placed in a beaker containing anhydrous ethanol and ultrasonically dispersed in an ultrasonic chamber. This process is repeated 2 to 3 times. The anhydrous ethanol containing carbides in the beaker is transferred to a filtration device, and the electrolyte containing carbides at the working electrode end is transferred to a filtration device. Anhydrous ethanol is used to wash the residual carbides on the beaker, electrolytic cell, and nylon filter membrane at the working electrode end into the filtration device. The remaining sample surface is cleaned and dried. The total weight of the sample after electrolytic extraction is weighed to be 12.3457 g.

[0044] The anode mud produced in the electrolysis process was filtered out, and anhydrous ethanol was used to rinse 4 to 5 times during the filtration process to obtain pure carbide on the nylon filter membrane. The nylon filter membrane containing the carbide was placed in a drying oven for drying, and the carbide obtained was collected and weighed, and its total mass was 0.1832 g; the morphology of the collected carbide is as follows Figure 3 , XRD results are as follows Figure 4 , the particle size distribution diagram is as follows Figure 5 It can be seen from the figure that the carbides obtained by electrolytic extraction from austenitic wear-resistant steel are VC and NbTiC2, and the size distribution is about 100 to 2000nm.

[0045] Example 2

[0046] This embodiment uses bainite wear-resistant steel as the working electrode of electrolytic extraction, which specifically includes the following steps:

[0047] (1) Prepare an electrolyte solution according to the ratio of 28 g tartaric acid, 15 g potassium chloride, and 500 mL deionized water.

[0048] (2) Use 240-2000 mesh sandpaper to remove oxides from the surface of the wear-resistant steel sample, place it in a beaker filled with anhydrous ethanol and ultrasonically clean it for 10 minutes, dry the sample and weigh and record the sample weight. Prepare eight samples with a total mass of 16.9574 g.

[0049] (3) Install a working electrode and a reference electrode at one end of a 100 mL H-type replaceable membrane electrolytic cell, install a platinum electrode at the other end, fix two nylon filter membranes at the flange, and use flange clamps to fix the flanges at both ends; after the installation is completed, pour the electrolyte prepared in step (1) into the cell to immerse the three electrodes and the flange connection; connect the working electrode to the positive pole of the power supply as the anode, and the platinum electrode as the cathode, and keep the temperature of the electrolyte at room temperature; use a constant voltage polarization mode for electrolytic extraction, set the voltage to 3.4 V, the electrolysis time to 12 h, and start electrolysis.

[0050] (4) After all samples are electrolyzed, the samples are placed in a beaker containing anhydrous ethanol and ultrasonically dispersed in an ultrasonic environment. This process is repeated 2 to 3 times. The anhydrous ethanol containing carbides in the beaker is transferred to a filtration device, and the electrolyte containing carbides at the working electrode end is transferred to a filtration device. Anhydrous ethanol is used to wash the residual carbides on the beaker, electrolytic cell, and nylon filter membrane at the working electrode end into the filtration device. The remaining sample surface is cleaned and dried. The total weight of the sample after electrolytic extraction is weighed to be 12.6065 g.

[0051] The anode mud produced in the electrolysis process was filtered out, and anhydrous ethanol was used to rinse 4 to 5 times during the filtration process to obtain pure carbide on the nylon filter membrane. The nylon filter membrane containing the carbide was placed in a drying oven for drying, and the obtained carbide was collected and weighed, and its total mass was 0.1878 g; the morphology of the collected carbide is as follows Figure 6 , XRD results are as follows Figure 7 , the particle size distribution diagram is as follows Figure 8 ,It can be seen from the figure that the carbide obtained by electrolytic extraction from bainitic wear-resistant steel is TiC, and its size distribution is about 300 to 2000nm.

[0052] Example 3

[0053] This embodiment uses martensitic wear-resistant steel as the working electrode for electrolytic extraction, which specifically includes the following steps:

[0054] (1) Prepare an electrolyte solution according to the ratio of 25 g tartaric acid, 15 g potassium chloride, and 500 mL deionized water.

[0055] (2) Use 240-2000 mesh sandpaper to remove oxides from the surface of the wear-resistant steel sample, place it in a beaker filled with anhydrous ethanol and ultrasonically clean it for 10 minutes, dry the sample and weigh and record the sample weight. Prepare eight samples with a total mass of 16.5961 g.

[0056] (3) Install a working electrode and a reference electrode at one end of a 100 mL H-type replaceable membrane electrolytic cell, install a platinum electrode at the other end, fix two nylon filter membranes at the flange, and use flange clamps to fix the flanges at both ends; after the installation is completed, pour the electrolyte prepared in step (1) into the cell to immerse the three electrodes and the flange connection; connect the working electrode to the positive pole of the power supply as the anode, and the platinum electrode as the cathode, and keep the temperature of the electrolyte at room temperature; use a constant voltage polarization mode for electrolytic extraction, set the voltage to 3.4 V, the electrolysis time to 12 h, and start electrolysis.

[0057] (4) After all samples are electrolyzed, the samples are placed in a beaker containing anhydrous ethanol and ultrasonically dispersed in an ultrasonic environment. This process is repeated 2 to 3 times. The anhydrous ethanol containing carbides in the beaker is transferred to a filtration device, and the electrolyte containing carbides at the working electrode end is transferred to a filtration device. Anhydrous ethanol is used to wash the residual carbides on the beaker, electrolytic cell, and nylon filter membrane at the working electrode end into the filtration device. The remaining sample surface is cleaned and dried. The total weight of the sample after electrolytic extraction is weighed to be 11.9149 g.

[0058] The anode mud produced during the electrolysis process was filtered out and rinsed with anhydrous ethanol 4 to 5 times during the filtration process to obtain pure carbide on the nylon filter membrane. The nylon filter membrane containing the carbide was placed in a drying oven for drying, and the obtained carbide was collected and weighed, with a total mass of 0.2254 g. The morphology of the collected carbide is as follows: Fig. 9 , XRD results are as follows Fig.10 , the particle size distribution diagram is as follows Fig.11 It can be seen from the figure that the M7C3 type carbide is obtained by electrolytic extraction from martensitic wear-resistant steel, and the size distribution is about 500 to 1000nm.

[0059] Comparative Example 1

[0060] This embodiment uses austenitic wear-resistant steel as the working electrode of electrolytic extraction, which specifically includes the following steps:

[0061] (1) Prepare an electrolyte solution according to the ratio of 15 g tartaric acid, 20 g potassium chloride, and 500 mL deionized water.

[0062] (2) Use 240-2000 mesh sandpaper to remove oxides from the surface of the wear-resistant steel sample, place it in a beaker filled with anhydrous ethanol and ultrasonically clean it for 10 minutes, dry the sample and weigh and record the sample weight. Prepare eight samples with a total mass of 17.2147 g.

[0063] (3) In a 100 mL H-type replaceable membrane electrolytic cell, a working electrode and a reference electrode were installed at one end, and a platinum electrode was installed at the other end. Two nylon filter membranes were fixed at the flange port, and the flange ports at both ends were fixed with flange clamps; three electrodes were connected, with the working electrode as the anode and the platinum electrode as the cathode. The temperature of the electrolyte was maintained at room temperature, and electrolytic extraction was performed using a constant voltage polarization mode, with the voltage set to 3.8 V and the electrolysis time set to 8 h. After completion, the electrolyte was poured in, and electrolysis was started after the three electrodes and the flange connection port were immersed.

[0064] (4) After all samples are electrolyzed, the samples are placed in a beaker containing anhydrous ethanol and ultrasonically dispersed in an ultrasonic chamber. This process is repeated 2 to 3 times. The anhydrous ethanol containing carbides in the beaker is transferred to a filtration device, and the electrolyte containing carbides at the working electrode end is transferred to a filtration device. Anhydrous ethanol is used to wash the residual carbides on the beaker, electrolytic cell, and nylon filter membrane at the working electrode end into the filtration device. The remaining sample surface is cleaned and dried. The total weight of the sample after electrolytic extraction is weighed to be 12.4961 g.

[0065] The anode mud produced in the electrolysis process was filtered out, and anhydrous ethanol was used to rinse 4 to 5 times during the filtration process to obtain pure carbide on the nylon filter membrane. The nylon filter membrane containing the carbide was placed in a drying oven for drying, and the obtained carbide was collected and weighed, and its total mass was 0.2154 g; the XRD results are as follows: Fig.12 ,It can be seen from the figure that in addition to carbides, MnS also exists in the powder obtained by electrolytic extraction of austenitic wear-resistant steel.

[0066] By comparison, it can be seen that insufficient amount of tartaric acid cannot dissolve MnS inclusions in austenitic wear-resistant steel.

[0067] Comparative Example 2

[0068] This embodiment uses austenitic wear-resistant steel as the working electrode of electrolytic extraction, which specifically includes the following steps:

[0069] (1) Prepare an electrolyte solution according to the ratio of 5 g tartaric acid, 20 g potassium chloride, and 500 mL deionized water.

[0070] (2) Use 240-2000 mesh sandpaper to remove oxides from the surface of the wear-resistant steel sample, place it in a beaker filled with anhydrous ethanol and ultrasonically clean it for 10 minutes, dry the sample and weigh and record the sample weight. Prepare eight samples with a total mass of 17.8436 g.

[0071] (3) Install the working electrode and reference electrode at one end of a 100 mL H-type replaceable membrane electrolytic cell, install a platinum electrode at the other end, fix two nylon filter membranes at the flange, and use flange clamps to fix the flanges at both ends. Connect the three electrodes, with the working electrode as the anode and the platinum electrode as the cathode. Keep the electrolyte at room temperature, use the constant voltage polarization mode for electrolytic extraction, set the voltage to 3.8 V, and the electrolysis time to 8 h. After completion, pour the electrolyte, immerse the three electrodes and the flange connection, and start electrolysis.

[0072] (4) After all samples are electrolyzed, the samples are placed in a beaker containing anhydrous ethanol and ultrasonically dispersed in an ultrasonic chamber. This process is repeated 2 to 3 times. The anhydrous ethanol containing carbides in the beaker is transferred to a filtration device, and the electrolyte containing carbides at the working electrode end is transferred to a filtration device. Anhydrous ethanol is used to wash the residual carbides on the beaker, electrolytic cell, and nylon filter membrane at the working electrode end into the filtration device. The remaining sample surface is cleaned and dried. The total weight of the sample after electrolytic extraction is weighed to be 14.2023 g.

[0073] The anode mud produced in the electrolysis process was filtered out, and anhydrous ethanol was used to rinse 4 to 5 times during the filtration process to obtain pure carbide on the nylon filter membrane. The nylon filter membrane containing the carbide was placed in a drying oven for drying, and the obtained carbide was collected and weighed, and its total mass was 0.1675 g; the XRD results are as follows: Fig.13 ,It can be seen from the figure that in addition to carbides, MnS also exists in the powder obtained by electrolytic extraction of austenitic wear-resistant steel.

[0074] By comparison, it can be seen that insufficient amount of tartaric acid cannot dissolve MnS inclusions in austenitic wear-resistant steel.

[0075] Excess tartaric acid will destroy the carbide.

[0076] The obtained electron microscope pictures of the carbides show that the electrolyte used in the present invention can obtain complete carbides, and the carbides will not be destroyed in this acidic environment.

[0077] By collecting complete and pure carbides, and by particle size analysis and mass fraction calculation, the carbides in the steel can be quantitatively analyzed; the following table shows the mass percentage of carbides collected in the embodiment.

[0078] Table 1 Carbide mass fractions of examples and comparative examples

[0079]

[0080] The XRD test results show that the present invention can effectively extract carbides from austenite, bainite and martensite wear-resistant steels. No peaks of inclusions and iron are observed in the XRD diagram of the embodiment, indicating that the electrolyte in the present invention can dissolve inclusions well and inhibit the generation of impurities, and the extraction device has a good physical isolation effect on the iron generated on the cathode; the XRD diagram of the comparative example can clearly observe the appearance of the MnS peak, indicating that impurities are generated in the comparative example, and the tartaric acid used in the present invention can dissolve inclusions at a suitable dosage, effectively improving the purity of the extracted carbides.

Claims

1. A method for extracting carbides from wear-resistant steel, characterized in that: The method comprises the following process steps: (1) preparing an electrolyte using tartaric acid, potassium chloride and deionized water; (2) Prepare the wear-resistant steel sample as the electrolytic sample required for electrolytic extraction, remove the oxide on the surface of the wear-resistant steel sample using 240-2000 mesh sandpaper, place it in a beaker filled with anhydrous ethanol and ultrasonically clean it for 5-10 minutes, then dry it and weigh the sample; (3) Use an H-type replaceable membrane electrolytic cell and install three electrodes, fix two nylon filter membranes at the flange, use flange clamps to fix the flanges at both ends, connect the working electrode to the positive pole of the power supply as the anode, and the platinum electrode as the cathode, and use a constant voltage polarization mode for electrolytic extraction; (4) placing the sample after electrolysis into a container containing anhydrous ethanol, and then placing it into an ultrasonic dispersion, repeating 2 to 3 times; transferring the anhydrous ethanol containing carbides to a suction filtration device; and also transferring the electrolyte containing carbides at the working electrode end to the suction filtration device; Use anhydrous ethanol to wash the residual carbides on the nylon filter membrane of the container, electrolytic cell and working electrode into the suction filtration device; (4) The remaining sample surface is cleaned and dried, and the weight of the sample after electrolytic extraction is obtained by weighing; the anode mud produced during the electrolysis process is filtered out, and it is rinsed with anhydrous ethanol for 4 to 5 times during the filtration process to obtain pure carbide on the nylon filter membrane, and the nylon filter membrane containing the carbide is placed in a drying oven for drying, and the obtained carbide is collected and weighed.

2. The method for extracting carbides from wear-resistant steel according to claim 1, characterized in that: In step (1), every 500 mL of electrolyte is prepared according to the ratio of 25-30 g of tartaric acid, 15-20 g of potassium chloride, and the balance of deionized water.

3. The method for extracting carbides from wear-resistant steel according to claim 1, characterized in that: The temperature of the electrolytic cell in step (3) is maintained at room temperature, the voltage of the constant voltage polarization mode is set to 3.4 to 3.8 V, and the electrolysis time is set to 6 to 12 h.

4. The method for extracting carbides from wear-resistant steel according to claim 1, characterized in that: The nylon filter membrane used in step (3) and step (5) has a pore size of Φ0.05 μm.

5. The method for extracting carbides from wear-resistant steel according to claim 1, characterized in that: The electrolyte in step (1) needs to be prepared and used immediately, and the purity of tartaric acid and potassium chloride is analytical grade.

6. The method for extracting carbides from wear-resistant steel according to claim 1, characterized in that: The steel sample in step (2) has a size of 10 mm×15 mm×2 mm and is fixed with a platinum sheet electrode clamp as a working electrode.

7. The method for extracting carbides from wear-resistant steel according to claim 1, characterized in that: Each H-type electrolytic cell in step (3) has a capacity of 100 mL.

8. The method for extracting carbides from wear-resistant steel according to claim 1, characterized in that: When installing the three electrodes in step (3), the working electrode and the reference electrode need to be installed in the same electrolytic cell, and the platinum sheet electrode needs to be installed in another electrolytic cell.

Citation Information

Patent Citations

  • Organic electrolyte, method for extracting non-metallic inclusions from steel and electrolyzer

    CN103898596A

  • Production method of transmission electron microscope sample

    CN104897452A

  • Method for extracting and separating oxide and sulfide in sulfur-containing free-cutting steel

    CN107621554A

  • Method for observing and analyzing inclusions in steel

    CN116500113A

  • Method for characterizing non-metallic inclusions in DZ125 alloy through sample electrolysis

    CN117110116A